2019
DOI: 10.33088/jmk.v11i2.365
|View full text |Cite
|
Sign up to set email alerts
|

Edukasi Melalui Peer Grup Berpengaruh Terhadap Pengetahuan Dan Sikap Tentang Personal Hygiene

Abstract: According to Riskesdas data in 2015, found most of the diseases that attack school-aged children are caused due to lack of personal hygiene. This is because the lack of knowledge of children will be personal hygiene. The purpose of this study to determine the effect of educational methods through peer group on knowledge and attitudes about personal hygiene. This type of research is pre experimental with one group pretest-posttest design. Samples taken amounted to 30 people using side porposive technique. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The results of the research conducted at semporkebumen-States that there is a difference in effectiveness in counseling conducted by the peer groupand counseling which is conducted by health workerswith a small range of values [2].In other studiesalso shows that there is influence education through peer groups against knowledgeand attitudes about personal hygiene in elementary school children in Bengkulu City in 2017. [4]. Changes in behaviorbased on changes in knowledge, the better the knowledge the better personal hygiene behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the research conducted at semporkebumen-States that there is a difference in effectiveness in counseling conducted by the peer groupand counseling which is conducted by health workerswith a small range of values [2].In other studiesalso shows that there is influence education through peer groups against knowledgeand attitudes about personal hygiene in elementary school children in Bengkulu City in 2017. [4]. Changes in behaviorbased on changes in knowledge, the better the knowledge the better personal hygiene behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Because teens often identify with their peers, presenting messages through these peer networks can increase the effectiveness of an education program's goal (Youth Tech Health, 2015). Research at SDN 37 Bengkulu City found that peer group education influenced the knowledge and attitudes of primary school children (Sibarani et al, 2019). Likewise the results of research at MTS Negeri 1 Bandung City that the implementation of peer education increases the knowledge, attitudes and self-efficacy of young women about puberty (Legiati et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Pendidikan kesehatan tentang personal hygiene penting untuk siswa agar mereka mempunyai informasi dan pengetahuan yang benar tentang personal hygiene dan mendorong perilaku hidup bersih dan sehat siswa. Berbagai metode dapat dilakukan dalam meningkatkan pengetahuan dan sikap siswa mengenai personal hygiene, seperti metode konvensional dengan penyuluhan maupun Peer Group Health Education (7). Untuk itu penelitian ini dilakukan untuk membandingkan efektifitas kedua metode tersebut.…”
Section: Pendahuluanunclassified
“…Pengetahuan seseorang tentang personal hygiene berpengaruh mendorong perilaku seseorang dalam menjaga dan merawat kesehatan diri serta mencegah terjadinya penularan penyakit. Terdapat berbagai metode dalam pendidikan kesehatan dalam meningkat perilaku personal hygiene, mulai dari metode konvensional hingga metode pengembangan seperti Peer Group Health Education (7).…”
Section: Pembahasanunclassified